All‐Solid‐State Asymmetric Supercapacitors with Metal Selenides Electrodes and Ionic Conductive Composites Electrolytes. (23rd July 2019) - Chen, Zhiyuan; Yang, Yongrui; Ma, Zhihao; Zhu, Tao; Liu, Lei; Zheng, Jie; Gong, Xiong
Abstract: All‐solid‐state flexible asymmetric supercapacitors (ASCs) are developed by utilization of graphene nanoribbon (GNR)/Co0.85 Se composites as the positive electrode, GNR/Bi2 Se3 composites as the negative electrode, and polymer‐grafted‐graphene oxide membranes as solid‐state electrolytes. Both GNR/Co0.85 Se and GNR/Bi2 Se3 composite electrodes are developed by a facile one‐step hydrothermal growth method from graphene oxide nanoribbons as the nucleation framework. The GNR/Co0.85 Se composite electrode exhibits a specific capacity of 76.4 mAh g −1 at a current density of 1 A g −1 and the GNR/Bi2 Se3 composite electrode exhibits a specific capacity of 100.2 mAh g −1 at a current density of 0.5 A g −1 . Moreover, the stretchable membrane solid‐state electrolytes exhibit superior ionic conductivity of 108.7 mS cm −1 . As a result, the flexible ASCs demonstrate an operating voltage of 1.6 V, an energy density of 30.9 Wh kg −1 at the power density of 559 W kg −1, and excellent cycling stability with 89% capacitance retention after 5000 cycles. All these results demonstrate that this study provides a simple, scalable, and efficient approach to fabricate high performance flexible all‐solid‐state ASCs for energy storage. Abstract : All‐solid‐state flexible asymmetric supercapacitors with the graphene nanoribbon/Co0.85 Se composites as the positive electrode, the graphene nanoribbon/Bi2 Se3 composites as the negative electrode, and the polymer‐grafted‐graphene oxide membranes as solid‐state electrolytes exhibit an operating voltage of 1.6 V, an energy density of 30.9 Wh kg −1 at the power density of 559 W kg −1, and excellent cycling stability with 89% capacitance retention after 5000 cycles.